Development and Optimization of Starch-Based Bioplastics from Millet and Cassava Using Mixture Design Approach - Aminu D. MAHMUD; Imran N. IBRAHIM (FUDMA Journal of Engineering and Technology, 2026)
The increasing environmental concerns associated with conventional petroleum-based plastics have driven the search for sustainable and biodegradable alternatives. This study investigates the extraction, characterization, and application of starches derived from millet (Pennisetum glaucum) and cassava (Manihot esculenta) for the production of bioplastic films. Starch was extracted using a wet extraction method and subsequently characterized for amylose and amylopectin content using iodine colorimetry. Bioplastic films were produced through solution casting with glycerol as a plasticizer, and the effects of varying starch blend ratios were evaluated using a simplex lattice mixture design. Results showed that cassava starch possessed a higher amylose content ( 27.93%), while millet starch exhibited lower amylose ( 18.17%) and higher amylopectin content. These compositional differences significantly influenced the mechanical and physical properties of the bioplastics. The tensile strength, strain, modulus of elasticity, and water absorption of the films were determined. Among the formulations, the 50:50 blend of millet and cassava starch demonstrated the best overall performance, exhibiting improved tensile strength and mechanical stability compared to single-starch films. However, all samples showed relatively high-water absorption, reflecting the hydrophilic nature of starch-based materials. Optimization using mixture design yielded a desirability value of 0.546, with predicted properties showing reasonable agreement with experimental results. The findings highlight the synergistic effect of starch blending in enhancing bioplastic performance and confirm the potential of locally sourced starches as viable raw materials for biodegradable plastic production. Nonetheless, further modifications are required to improve water resistance and broaden practical applications.